Nietzsche on consciousness and the embodied mind - Dries, Manuel (Monographien und Texte zur Nietzsche-Forschung ;, 2018)
Nietzsche's thought has been of renewed interest to philosophers in both the Anglo-American and the phenomenological and hermeneutic traditions. 'Nietzsche on Consciousness and the Embodied Mind' presents 16 essays from analytic and continental perspectives. Appealing to both international communities of scholars, the volume seeks to deepen the appreciation of Nietzsche's contribution to our understanding of consciousness and the mind. Over the past decades, a variety of disciplines have engaged with Nietzsche's thought, including anthropology, biology, history, linguistics, neuroscience, and psychology, to name just a few. His rich and perspicacious treatment of consciousness, mind, and body cannot be reduced to any single discipline, and has the potential to speak to many. And, as several contributors make clear, Nietzsche's investigations into consciousness and the embodied mind are integral to his wider ethical concerns.